Optimizing MoS2 Electrolyte‐Gated Transistors: Stability, Performance, and Sensitivity Enhancements - Steffen Rühl; Giovanni Ligorio; Max Heyl; Emil J. W. List‐Kratochvil (Advanced Electronic Materials)
Abstract Electrolyte‐gated field‐effect transistors (EGFETs) based on transition metal dichalcogenides (TMDCs) are promising for biosensing applications due to their high transconductance (1.98 mS) and surface sensitivity enabling the detection of minute interfacial changes. However, their stability in aqueous poses significant challenges for long‐term reliability. This work presents a study to anhance both the stability and performance of TMDC‐based EGFETs. Initial devices showed promising performance but suffered significant instability during prolonged aqueos operation, limiting their biosensing applications. Postmortem analysis identified key areas for improvement leadinf to three major modifications: 1) a double‐junction Ag/AgCl electrode to prevent ion leakage, 2) a protective resist layer to shields the monolayer, and 3) precise etching to confine the semiconductor material, reducing parasitic currents. These optimizations imroved the devices' transconductance and ensured stable operation over extended periods establishing TMDC‐based EGFETs as viable candidates for reliable biosensing in aqueous environments.